Mixed constraints in optimal control: an implicit function theorem approach - Maria do Rosário de Pinho (2007)
This paper concerns a derivation of second-order necessary conditions for a fixed-endpoint control problem of Lagrange involving mixed equality and/or inequality constraints, posed over piecewise continuous controls. These conditions are obtained in a clear and transparent way by reducing the original problem, through an implicit function theorem approach, to an unconstrained control problem.